Effects of postexercise protein intake on muscle mass and strength during resistance training: Is there an optimal ratio between fast and slow proteins? - Fabre, M.; Hausswirth, C.; Tiollier, E.; Molle, O.; Louis, J.; Durguerian, A.; Neveux, N.; Bigard, X. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
While effects of the two classes of proteins found in milk (i.e., soluble proteins, including whey, and casein) on muscle protein synthesis have been well investigated after a single bout of resistance exercise (RE), the combined effects of these two proteins on the muscle responses to resistance training (RT) have not yet been investigated. Therefore, the aim of this study was to examine the effects of protein supplementation varying by the ratio between milk soluble proteins (fast-digested protein) and casein (slow-digested protein) on the muscle to a 9-week RT program. In a double-blind protocol, 31 resistance-trained men, were assigned to 3 groups receiving a drink containing 20g of protein comprising either 100% of fast protein (FP(100), n = 10), 50% of fast and 50% of slow proteins (FP(50), n = 11) or 20% of fast protein and 80% of casein (FP(20), n = 10) at the end of training bouts. Body composition (DXA), and maximal strength in dynamic and isometric were analyzed before and after RT. Moreover, blood plasma aminoacidemia kinetic after RE was measured. The results showed a higher leucine bioavailability after ingestion of FP(100) and FP(50) drinks, when compared with FP(20) (p< .05). However, the RT-induced changes in lean body mass (p < .01), dynamic (p < .01), and isometric muscle strength (p < .05) increased similarly in all experimental groups. To conclude, compared with the FP(20) group, the higher rise in plasma amino acids following the ingestion of FP(100) and FP(50) did not lead to higher muscle long-term adaptations.